Evaluation of calcium hydroxide apexification in immature permanent incisors - Khidhair A Al-Jumaili; Baydaa AO Al-Rawi; Aisha A Qasim (University of Mosul, College of Dentistry, 2011)
Aims of the Study: The aim of the present study is to identify the effectiveness of tgpaste of calcium hydroxide with barium sulfate in inducing a calcified apical barrier of an incompletely formed root in necrotic permanent incisors of children. Materials and Methods: Twenty children with twenty teeth with pulpal necrotic and an incompletely formed apex were included in this study. Working length determination, instrumentation, irrigation and dryness were carried out for the root canals then paste of non setting calcium hydroxide injected inside the canal and after each 3 months the patients were recalled to check the calcified apical barrier formation. Results: The average age of patients was 8 years. The mean duration for apical barrier formation was 6.813+1.1 months (range 6-12 months). Discussion: The use of calcium hydroxide in apical barrier formation has shown promising results. Because of its enhanced success rate, easy availability for clinician and affordability for patients, it has gained widest acceptance all around the world. Conclusions: It is generally agreed that calcium hydroxide is the major ingredient responsible for stimulating the desired calcific closure of the apical area of non-vital immature permanent incisors.